Home Laundry Services / Mohd Azri Abdul Manan … [et al.] - Abdul Manan, Mohd Azri; Zainuddin, Afifuddinfitri; Shamshulbahri, Nur Amanina; Awang Jos, Dayang Nur Syaza; Mohd. Mahin, Mohd. Khalid (2018)
Home Laundry Services is basically a new business initiative that were founded by us to help people whose scheduled were packed with their routine activities especially to students and lecturers in Kota Samarahan. We can collect your laundry from your home and sent it back to our customers as fast as you could ever imagine because we provide home to home laundry services because we are desire to give our best service to the customers. We are desire to help those people who have a busy schedule and disabled residents in Kota Samarahan. The customers do not have to waste your time and energy to go to laundry as it was costly in terms of energy and money. This is because in our home-to home laundry services, we provide services which are affordable and cheaper compared to other laundry scattered through Desa Ilmu and Kota Samarahan. Apart from that, we also provide other services such as folding and also hand wash laundry. We can guaranteed you all that our laundry services was the best and in excellent quality in Kota Samarahan as we use high quality products to wash your laundry, with a well-managed and sophisticated machines to do your laundry. Because of these services provided, we believe that our business will become famously known by the nearby citizens in Kota Samarahan. If our business are going well, we will expand our business in the Kuching city or other regions in the future and achieve its target profit at least 2 years from now . We also believe that someday these business of ours potentially have a greater demand in the market because of people nowadays did not prefer to hand-wash their clothes or even go to the laundry by themselves.